Longevity of Posterior Composite Restorations: A Systematic Review and Meta-analysis. (October 2014) - Opdam, N.J.M.; van de Sande, F.H.; Bronkhorst, E.; Cenci, M.S.; Bottenberg, P.; Pallesen, U.; Gaengler, P.; Lindberg, A.; Huysmans, M.C.D.N.J.M.; van Dijken, J.W.
The aim of this meta-analysis, based on individual participant data from several studies, was to investigate the influence of patient-, materials-, and tooth-related variables on the survival of posterior resin composite restorations. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted a search resulting in 12 longitudinal studies of direct posterior resin composite restorations with at least 5 years' follow-up. Original datasets were still available, including placement/failure/censoring of restorations, restored surfaces, materials used, reasons for clinical failure, and caries-risk status. A database including all restorations was constructed, and a multivariate Cox regression method was used to analyze variables of interest [patient (age; gender; caries-risk status), jaw (upper; lower), number of restored surfaces, resin composite and adhesive materials, and use of glass-ionomer cement as base/liner (present or absent)]. The hazard ratios with respective 95% confidence intervals were determined, and annual failure rates were calculated for subgroups. Of all restorations, 2, 816 (2, 585 Class II and 231 Class I) were included in the analysis, of which 569 failed during the observation period. Main reasons for failure were caries and fracture. The regression analyses showed a significantly higher risk of failure for restorations in high-caries-risk individuals and those with a higher number of restored surfaces.